2020
DOI: 10.3389/fmicb.2019.03133
|View full text |Cite|
|
Sign up to set email alerts
|

Genome Sequencing and Comparative Analysis of Three Hanseniaspora uvarum Indigenous Wine Strains Reveal Remarkable Biotechnological Potential

Abstract: A current trend in winemaking has highlighted the beneficial contribution of non-Saccharomyces yeasts to wine quality. Hanseniaspora uvarum is one of the more represented non-Saccharomyces species onto grape berries and plays a critical role in influencing the wine sensory profile, in terms of complexity and organoleptic richness. In this work, we analyzed a group of H. uvarum indigenous wine strains as for genetic as for technological traits, such as resistance to SO 2 and β-glucosidase activity. Three strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 83 publications
1
11
0
Order By: Relevance
“…Hanseniaspora uvarum is an important yeast in the beverage industry, in particular for wine. In recent years, researchers have shown particular interest in this yeast, and reports on its beneficial impact on winemaking as well as several genome sequences have been published [ 34 , 35 , 36 , 37 ]. Despite the growing interest, to date, there are no genetic modification tools available for H .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hanseniaspora uvarum is an important yeast in the beverage industry, in particular for wine. In recent years, researchers have shown particular interest in this yeast, and reports on its beneficial impact on winemaking as well as several genome sequences have been published [ 34 , 35 , 36 , 37 ]. Despite the growing interest, to date, there are no genetic modification tools available for H .…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the increasing importance of Hanseniaspora in wine fermentations, only in the past couple of years, has large-scale genome sequencing provided information on Hanseniaspora species [ 34 , 35 , 36 , 37 ]; this wealth of information provides a basic framework for analysing the biology of Hanseniaspora . Recent research has shown that the low specific activity of pyruvate kinase, catalysing one of the rate limiting steps in the glycolytic pathway, could explain the reduced capacity of Hanseniaspora to form ethanol [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to Saccharomyces, among Hanseniaspora strains, the ability to tolerate this antiseptic is undoubtedly a rare characteristic (Grangeteau et al, 2016). The H. uvarum strains tested in this study were already selected for sulphur dioxide tolerance (Guaragnella et al, 2020), and consequently, we tested these three H. uvarum S. cerevisiae, has determined differences statistically significant among the wines obtained by mixed and single starters (Table 1). These results confirmed that when yeast strains developed together in mixed fermentations, they do not grow together passively, but rather, they interact each other, producing different compounds or different amounts of compounds affecting the chemical and aromatic composition of wines (Anfang, Brajkovich, & Goddard, 2009;Ciani et al, 2016;Ciani, Comitini, Mannazzu, & Domizio, 2010;Howell, Cozzolino, Bartowsky, Fleet, & Henschke, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The two S. cerevisiae strains were previously selected, on the basis of interesting enological traits (Capece, Romaniello, Siesto, & Romano, 2012; Siesto, Capece, Sipiczki, Csoma, & Romano, 2013). The three H. uvarum strains were selected for their low production level of acetic acid and high β‐glucosidase activity (Capece et al, 2005; Guaragnella et al, 2020). All the yeasts were maintained on yeast extract‐peptone‐dextrose (YPD) medium (1% yeast extract; 2% peptone; 2% glucose; 2% agar) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation